Penerapan Sistem Informasi Akuntansi dalam Instansi Pendidikan: (SDN Babelan Kota 06) - Adelia Pramesti Handayani; Syaefani Safitri Tussadiah; Azzahra Isnaeni Tatsbita; Fadhlika Dwi Larasati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the use of the School Activity Plan and Budget Application System (ARKAS) in managing BOS funds at elementary schools in Bekasi Regency. The study employs qualitative methods through interviews and literature reviews from various sources. It was conducted at SDN Babelan Kota 06. The implementation of ARKAS version 4.0 significantly contributes to budget management in Indonesian schools. ARKAS facilitates online budget planning, submission, and tracking, as well as automated reporting and system integration to enhance transparency and accountability. However, ARKAS implementation faces challenges such as lack of understanding and training in schools, technological infrastructure limitations, and frequent policy changes. The study highlights the importance of better socialization and adaptation to regulatory changes to improve the effectiveness of ARKAS in school fund management.